GRB 080503: A Very Early Blue Kilonova and an Adjacent Nonthermal Radiation Component - Hao Zhou; Zhi-Ping Jin; Stefano Covino; Lei Lei; Yu An; Hong-Yu Gong; Yi-Zhong Fan; Da-Ming Wei (The Astrophysical Journal, 2023)
The temporal behavior of the very dim optical afterglow of GRB 080503 is at odds with the regular forward shock afterglow model and a sole kilonova component responsible for optical emission has been speculated in some literature. Here we analyze the optical afterglow data available in archive and construct time-resolved spectra. The significant detection by Keck I in G/R bands at t ∼ 3 days, which has not been reported before, as well as the simultaneous Gemini-North r -band measurement, are in favor of a power-law spectrum that is well consistent with the optical to X-ray spectrum measured at t ∼ 4.5 days. However, for t ≤ 2 days, the spectrum is thermal-like and a straightforward interpretation is a kilonova emission from a neutron star merger, making it, possibly, the first detection of a very early kilonova signal at t ∼ 0.05 day. A nonthermal nature of optical emission at late times ( t ∼ 2 days), anyhow, cannot be ruled out because of the large uncertainty of the g -band data. We also propose to classify the neutron star merger induced optical transients, according to the temporal behaviors of the kilonova and the nonthermal afterglow emission, into four types. GRB 080503 would then represent the first observation of a subgroup of neutron star merger driven optical transients (i.e., type IV) consisting of an early blue kilonova and an adjacent nonthermal afterglow radiation.